The image of nomadism in Russian reality: Образ номадизма в российской действительности - Shlyakov, Aleksei (Przegląd Wschodnioeuropejski, 2020)
The article reveals the specific features of nomadism on the basis of an analysis of the work of poststructuralists, social philosophers. These include the increase in the speeds and frequency of movements of material and virtual objects; blurring the line between Home and work due to the proliferation of the Internet; short duration and simulative interpersonal contacts; a change in the topology of a social space designed according to the principles of a smooth and rhizome space in metropolis, which leads to a nonstop movement. It has been established that in Russian reality manifestations of nomadism can be found in the design and use of spaces of large cities, in the motorization of the population, the development of international and domestic tourism, as well as the emergence of the phenomenon of digital nomads.